Salafi Ritual Purity : In the Presence of God. - Gauvain, Richard (Majmūʻah-ʼi ʻulūm va maʻārif-i Islāmī., 2012)
Since 9/11, Salafism has attracted a great deal of attention from the world's media, which predominantly focuses on its potential for revolutionary violence. Salafism remains poorly understood both in Western media, where it is now the focus of considerable debate, and in Western academia, where until recently it was virtually undiscussed. In neither arena has a consensus emerged regarding what Salafism is or does. This pioneering work fills this lacuna by redirecting the reader towards the sphere of ritual practice, within which the discussions of contemporary Salafi scholars prove.